COMMUNICATION PRIVACY MANAGEMENT: STUDI LITERATUR PADA BATASAN PRIVASI DALAM KONTEKS KELUARGA INDONESIA - Jasmine Alya Pramesthi; Putri Eka Wulandari; Irwansyah Irwansyah (Jurnal Ranah Komunikasi, 2020)
Each individual has their own privacy limits, this can be instructed by each individual who manages their privacy. One of the close relationships between individuals and other individuals is in the context of the family. Through the theory of Communication Privacy Management (CPM), this study explains how personal information is managed in the context of Indonesian families. This study uses a qualitative approach, namely a literature review. Literature review studies were carried out on various international studies published in the 2010-2020 timeframe where the research was carefully obtained through Google Scholar with predetermined criteria. The results showed that Communication Privacy Management (CPM) has involvement in the implementation of individuals regarding the limits or thin boundaries (permeability limits) of joint ownership of personal information in the context of the Indonesian family.